Vaccine-associated complications: a comparative multicenter evaluation among dental practitioners and dental students-which candidate vaccine is more safe in SARS COV II, Gam-COVID-Vac (Sputnik V), ChAdOx1 nCoV-19 (AstraZeneca), BBV152 (Covaxin), or BBIBP-CorV(Sinopharm)? - Behzad Houshmand; Seied Omid Keyhan; Hamid Reza Fallahi; Shaqayeq Ramezanzade; Erfan Sadeghi; Parisa Yousefi (SpringerOpen, 2022)
Abstract Background The rapidly developed vaccines against the severe acute respiratory syndrome coronavirus 2 carry a risk of provoking side effects. This study aimed to evaluate current vaccination non-serious/serious side effects. Methods A multicenter electronic questionnaire via an online platform was conducted over a 1-week period among vaccinated dental staff and dental students inquiring whether they experienced vaccine-related side-effects after vaccine administration. Results A total of 1205 respondents with a mean age of 39 (SD: 12) were retained for the analyses. The following vaccines were reported; Gam-COVID-Vac (Sputnik V), ChAdOx1 nCoV-19 (AstraZeneca), BBV152 (Covaxin), or BBIBP-CorV (Sinopharm). The majority of respondents received ChAdOx1 nCoV-19 (51.1%) and Gam-COVID-Vac (37.6%). The symptoms most frequently reported after vaccination were fatigue (79%), local pain in the injection site (77.4%), malaise (73%), and body pain (71.1%). Enrollees reported more onset of reactions on 0-12 h (44.1%) and 12-24 h (29.0%) after vaccine administration (p value <0.001). In 75.7%, the side effects last for up to 3 days. Merely 5.5% of cases reported the presence of side effects after the first week. Individuals with a history of SARSCoV-2 and other infections (MERS, influenza, and EBV) were more likely to report a number of unserious systemic side effects. Conclusion The commonly reported adverse events were in line with similar studies. We have concerns with the frequency of serious adverse effects. This work necessitates the need for further clinical assessments with larger sample sizes.